2013
DOI: 10.4103/0973-1296.117867
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo studies of an aqueous extract of Matricaria recutita (German chamomile) on the radiolabeling of blood constituents, on the morphology of red blood cells and on the biodistribution of the radiopharmaceutical sodium pertechnetate

Abstract: Background:Natural products might alter the labeling of blood constituents with technetium-99m (99mTc) and these results may be correlated with modifications of the shape of the red blood cells (RBC). The biodistribution of radiopharmaceuticals can be also altered.Objective:This investigation aimed to determine biological effects of an aqueous extract of chamomile (CE).Materials and Methods:To study the effect of the CE on the labeling of blood constituents with 99mTc, in vitro and in vivo assays were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It has been used as an emmenagogue and a uterine tonic in women. It is also effective in arthritis, back pain, brain tonic, bedsores and stomach cramps [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…It has been used as an emmenagogue and a uterine tonic in women. It is also effective in arthritis, back pain, brain tonic, bedsores and stomach cramps [30][31][32][33][34][35].…”
Section: Resultsmentioning
confidence: 99%
“…Plasma proteins and RBCs labeled with 99m Tc have been used to evaluate various clinical applications [32,34,35] and in experimental models [25][26][27][28][29][30]36].…”
Section: Discussionmentioning
confidence: 99%
“…In one case report, 99m Tc RBCs were used to localize intrathoracic bleeding [24]. Authors reported that synthetic and natural medications might alter the bioavailability of radiopharmaceuticals [25,26], as well as the radiolabeling of blood constituents [25,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aqueous extract of Matricaria recutita also alters the RBC morphology 10 . Similarly the interaction between the drugs and plasma membrane has been studied by different techniques previously 11,12 .…”
Section: Methodsmentioning
confidence: 99%